DETAILED LIST OF INVENTORY ON THE COOPERATIVE KOKARINDO PT. RNI USING MICROSOFT VISUAL FOXPRO 7.0 - Indra Syahrurozi; Sahni Damerianta Purba, SKom, MMSI (Jurnal Sistem Informasi, 2003)
Using a computer system as a tool gave the best result can also minimize the occurrence of errors or duplication of data collection from scratch. With the existence of computerized system and application programs use a structured and encouraging. on the inventory can be dipermudahkan in the process of searching for data processing and data entry or exit of goods and the form of reports or information on existing inventory.